An evaluation of interactive stacked bar charts. (26th March 2009) - Abell, Walter; Churcher, Clare; Lee, Jason
Interactivity is considered an important feature of visualisation software. This paper evaluates the addition of simple interactive features to the display of stacked bar charts. These features allow the user to move different data series onto the chart baseline and to query segment and total values. This approach is evaluated in a software trial where users answer questions based on various bar charts, some interactive and some static. The results show that the interactive features are useful in some cases, but do not always help the user to better interpret the charts.